EFEKTIVITAS PIJAT PUNGGUNG TERHADAP KELANCARAN ASI IBU POST PARTUM SECTIO CESAREA (Studi di Rumah Sakit Umum Daerah dr. Mohammad Zyn Sampang) - Qurrotu aini; Merlyna Suryaningsih (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
ABSTRACT In labor action Sectio Caesarea ( SC) is often the mother not being able to breastfeed the baby in the first hours after birth, especially if the mother is given general anesthesia. The condition of the surgical wound in the abdomen makes the breastfeeding process a little hampered. The results of the preliminary study found that 5 breastfeeding respondents did not come out, 4 breastfeeding respondents were not fluent, and 1 breastfeeding respondent was fluent. So it can be concluded that there are still postpartum SC mothers who experience irregular milk production. The purpose of this study was to analyze differences in the smoothness of milk production in postpartum SC mothers after back massage. This research method is Quasy Experiment pretest posttest design group . The independent variable is back massage while the dependent variable is the smoothness of breast milk production . The total population is 17 respondents, the number of samples is 10 Postpartum SC mothers . The sampling technique uses incidental sampling , the research instrument uses an observation sheet. Statistical test using the Wilcoxon test with α (0.05). Wilcoxon test showed that there were differences in the smoothness of milk production before and after being given a back massage with a p-value of 0.02 < 0.05. It is hoped that health workers can improve services regarding the smooth production of breast milk by teaching back massage techniques as an additional therapy to increase the smooth production of breast milk